Cancer Trials Ireland (ICORG) 06-34: A multi-centre clinical trial using three-dimensional conformal radiation therapy to reduce the toxicity of palliative radiation for lung cancer. Issue 2 (May 2018) - McDermott, Ronan L.; Armstrong, John G.; Thirion, Pierre; Dunne, Mary; Finn, Marie; Small, Cormac; Byrne, Mary; O'Shea, Carmel; O'Sullivan, Lydia; Shannon, Aoife; Kelly, Emma; Hacking, Dayle J.
Abstract: Title: Cancer Trials Ireland (ICORG) 06-34: A multi-centre clinical trial using three-dimensional conformal radiation therapy to reduce the toxicity of palliative radiation for lung cancer. NCT01176487. Background & purpose: Trials of radiation therapy for the palliation of intra-thoracic symptoms from locally advanced non-small cell lung cancer (NSCLC) have concentrated on optimising fractionation and dose schedules. In these trials, the rates of oesophagitis induced by this "palliative" therapy have been unacceptably high. In contrast, this non-randomised, single-arm trial was designed to assess if more technically advanced treatment techniques would result in equivalent symptom relief and reduce the side-effect of symptomatic oesophagitis. Materials & methods: Thirty-five evaluable patients with symptomatic locally advanced or metastatic NSCLC were treated using a three-dimensional conformal technique (3-DCRT) and standardised dose regimens of 39 Gy in 13 fractions, 20 Gy in 5 fractions or 17 Gy in 2 fractions. Treatment plans sought to minimise oesophageal dose. Oesophagitis was recorded during treatment, at two weeks, one month and three months following radiation therapy and 3–6 monthly thereafter. Mean dose to the irradiated oesophagus was calculated for all treatment plans. Results: Five patients (14%) had experienced grade 2 oesophagitis or dysphagia or both during treatment and 2 other patients had these side effects at the 2-week follow-up. At follow-up of one month after therapy, there was no grade two or higher oesophagitis or dysphagia reported. 22 patients were eligible for assessment of late toxicity. Five of these patients reported oesophagitis or dysphagia (one had grade 3 dysphagia, two had grade 2 oesophagitis, one of whom also had grade 2 dysphagia). Quality of Life (QoL) data at baseline and at 1-month follow up were available for 20 patients. At 1-month post radiation therapy, these patients had slightly less trouble taking a short walk, less shortness of breath, did not feel as weak, had better appetite and generally had a better overall quality of life than they did at baseline. They did report being slightly more tired. Conclusions: This trial is the first of its kind showing that 3-DCRT provides patients with lower rates of oesophageal toxicity whilst yielding acceptable rates of symptom control. (Sponsored by Cancer Trials Ireland (ICORG) Study number 06-34, the Friends of St. Luke's and the St. Luke's Institute of Cancer Research.)